Compact Planar Super-Wideband Antenna with Band-Notched Function - Shahsavari, H.; Nourinia, J.; Shirzad, H.; Shokri, M.; Asiaban, S.; Amiri, Zh.; Virdee, B. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the design of a novel printed monopole antenna is presented that operates across a super wideband frequency range (2.39 GHz to 40 GHz) and exhibits bandnotch characteristic that is necessary to eradicate interference from WLAN systems operating between 5.15 GHz ? 5.825 GHz. The prototype antenna consists of a radiating patch in the shape of an octagonal ring structure and embedded within ring is a rectangular strip. The antenna is excited through a microstrip feed-line and includes an elliptically shaped ground-plane that is defected with a dielectric notch in the vicinity of the patch. The proposed antenna’s structure is simple to design and is relatively inexpensive to fabricate. In addition, it is compact in size with overall dimensions of 30 × 30 × 1.6 mm3. The measured results confirm the impedance bandwidth cover a super wideband frequency range from 2.3 GHz ? 40 GHz, for VSWR ? 2 that corresponds to a fractional bandwidth of 178 %. The radiation characteristic of the proposed antenna is approximately omni-directional.